2015
DOI: 10.1002/adem.201400412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interface Evolution on Thermal Conductivity of Vacuum Hot Pressed SiC/Al Composites

Abstract: The SiC/Al composites have been fabricated by a vacuum hot pressing (VHP) process in order to study the effect of interface evolution on the global thermal conductivity (TC). By optimizing the VHP parameters of sintering temperature and time, the three different kinds of SiC/Al interface configurations, that is, non-bonded, diffusion-bonded, and reaction-bonded interfaces, are formed and identified by measurement of relative density, X-ray diffraction, scanning and (high-resolution) transmission electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…It is well-known that interfacial bonding states, namely non-bonded, diffusion-bonded and reactionbonded interfaces, can have a significant impact on global TC of MMCs whatever the employed VHP or SPS fabrication techniques. It has previously been demonstrated in VHPed SiC/Al composites that the formation of the nanoscale diffusion-bonded interface is the most favorable for TC enhancement [21]. This experimental result is also in good agreement with our predictive model since it is expected that the diffusion-bonded interface can provide not only necessary bonding strength but also low ITR [22].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is well-known that interfacial bonding states, namely non-bonded, diffusion-bonded and reactionbonded interfaces, can have a significant impact on global TC of MMCs whatever the employed VHP or SPS fabrication techniques. It has previously been demonstrated in VHPed SiC/Al composites that the formation of the nanoscale diffusion-bonded interface is the most favorable for TC enhancement [21]. This experimental result is also in good agreement with our predictive model since it is expected that the diffusion-bonded interface can provide not only necessary bonding strength but also low ITR [22].…”
Section: Introductionsupporting
confidence: 89%
“…Hence, enough attention should be paid to reevaluate feasibility of the SPS technique for potential applications in MMCs. Regarding the key issue of interface engineering, the conventional VHP technique is definitively more feasible than the SPS technique to allow the unique -if any-diffusion-bonded interfacial state to be tailored, in the diamond/Al composite (at the micrometer scale) and in the SiC/Al composite (at the nanoscale) [21], in order to maximize the effectiveness of TC enhancement. In the SPS case, the TC enhancement is possible but less effective by only increasing the amount of diffusionbonded interface in the sample.…”
Section: Demonstration Of Macroscopic Thermal Gradients In Rapid Heating-cooling Mode Generated During Spsmentioning
confidence: 99%
“…It is vitally important to develop thermal management materials with high thermal conductivity (TC) and tailored coefficient of thermal expansion (CTE) values to minimize thermal stresses [1,2]. Metal matrix composites combining the high TC of metal and low CTE of the reinforcement can be suitable candidates for electronic packaging materials [3]. Recently, GFs-reinforced copper matrix composites have gained much attention due to their excellent thermal properties, low density, and good machinability.…”
Section: Introductionmentioning
confidence: 99%
“…M. Chmielewski et al [ 11 ] investigated Cu-AlN metal matrix composites with a ceramic volume fraction between 0.1 and 0.4 prepared by a hot-pressing method in vacuum, the experimental results showed that 60Cu-40AlN composites exhibited a low CTE and high thermal conductivity coefficient of 10 × 10 −6 /K and 164.4 W/mK, respectively. Chen et al [ 12 ] fabricated SiC/Al composites with thermal conductivity of around 270 W/mK by a vacuum hot pressing (VHP) process at 655 °C. Wang et al [ 13 ] fabricated 3D-SiC/Al-Si-Mg interpenetrating composite (IPC) with three dimensional mutually interpenetrated structure by mold-forming and pressureless infiltration method.…”
Section: Introductionmentioning
confidence: 99%